2018
DOI: 10.1038/s41598-018-24258-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ageing and osteoarthritis on the mechanical properties of cartilage and bone in the human knee joint

Abstract: Osteoarthritis is traditionally associated with cartilage degeneration although is now widely accepted as a whole-joint disease affecting the entire osteochondral unit; however site-specific cartilage and bone material properties during healthy ageing and disease are absent limiting our understanding. Cadaveric specimens (n = 12; 31–88 years) with grades 0–4 osteoarthritis, were dissected and spatially correlated cartilage, subchondral and trabecular bone samples (n = 8 per cadaver) were harvested from femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 54 publications
10
109
0
Order By: Relevance
“…Investigating the BMI effect on BV/TV, we found a weak and non-significant relationship between BV.TV and BMI for medial samples, whereas Reina et al found a moderately significant relationship 32 . Like the Peters et al study, we found no link between BMI and tissue elastic modulus 30 . These findings suggest that BMI should not have a major effect on STB tissue elastic modulus.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Investigating the BMI effect on BV/TV, we found a weak and non-significant relationship between BV.TV and BMI for medial samples, whereas Reina et al found a moderately significant relationship 32 . Like the Peters et al study, we found no link between BMI and tissue elastic modulus 30 . These findings suggest that BMI should not have a major effect on STB tissue elastic modulus.…”
Section: Discussionsupporting
confidence: 62%
“…Peters et al found no difference in trabecular bone elastic tissue modulus at different stages in the disease 30 . However their subjects presented less severe OA and their samples were tested dehydrated.…”
Section: Discussionmentioning
confidence: 96%
“…The modulus of the composite was more similar to the modulus of cartilage (2.4-10 MPa) (Beck et al, 2016) than to that of trabecular bone (10.75-13.66 GPa) (Peters et al, 2018), thus mimicking the soft callus formed during natural bone healing. Therefore, a bone defect treated with this composite would still require additional fixation to restrain the defect site.…”
Section: Discussionmentioning
confidence: 75%
“…Tensile tests on whole bones reported in 1976, showed only moderate differences between bones from humans at different ages (54). Recently, micro-/nano-indentation tests revealed that the mechanical properties of human cortical (55) and trabecular (56) bones were remarkably constant as a function of age. The elastic modulus of murine growth plate are reported to be significantly different between the embryonic stage and postnatal stage, age 2 week, but did not vary significantly through the next growth stages until adulthood (up to age 4 months) (25).…”
Section: Resultsmentioning
confidence: 99%